A Case Report of Paralytic Patient Associated with Diabetes Mellitus - Byoung-woo Kim (Korean Pharmacopuncture Institute, 2009)
Objectives : This report aimed to study of paralytic patient associated with Diabetes Mellitus. Methods : Diabetes Mellitus has one of the highest death rate, because of it induces various complications. Especially paralytic patients who associated with diabetes mellitus are slow in recovery and easy to induce many complications. So control of the diabetes mellitus is the most important thing to treatment. We observed and treated with Cheunhwasangamibang and acupunture. Results : The paralytic patient with Diabetes Mellitus was treatment with Cheunhwasangamibang and improvement was seen. Conclusions : Results in this case support a role for Cheunhwasangamibang in controlling Diabetes Mellitus